1999
DOI: 10.1097/00007890-199905270-00012
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-?? Is Necessary for Initiating the Acute Rejection of Major Histocompatibility Complex Class Ii-Disparate Skin Allografts1

Abstract: The data demonstrate that IFNgamma is not necessary for generating effector mechanisms associated with acute transplant rejection but that it is required for initiating alloimmune responses to MHC class II-disparate skin grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 13 publications
5
39
0
Order By: Relevance
“…1), indicating that islet donor-derived IFN-␥ is not responsible for the rejection observed in IFN-␥-deficient hosts. Thus IFN-␥, like perforin and FasL, does not appear to be generally required for the overall rejection response, a result consistent with findings in other models (16,32,33).…”
Section: Islet Allografts Are Rejected By Immunocompetent Ifn␥-deficsupporting
confidence: 88%
See 2 more Smart Citations
“…1), indicating that islet donor-derived IFN-␥ is not responsible for the rejection observed in IFN-␥-deficient hosts. Thus IFN-␥, like perforin and FasL, does not appear to be generally required for the overall rejection response, a result consistent with findings in other models (16,32,33).…”
Section: Islet Allografts Are Rejected By Immunocompetent Ifn␥-deficsupporting
confidence: 88%
“…In accordance with these observations, Ring et al (32) recently showed that host-derived IFN-␥ is required for the efficient rejection of MHC class II-disparate skin allografts by CD4 ϩ T cells. However, rejection of fully allogeneic heart (33) and skin (16,32) grafts has been clearly shown to occur in the absence of hostderived IFN-␥, suggesting that there must also exist IFN-␥-independent mechanisms of allograft destruction. In contrast, IFN-␥ also appears to be required for the induction of allograft tolerance following costimulatory blockade, perhaps due to the inhibitory effect of this cytokine on T cell proliferation (15,16,34).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…After withdrawal of immunosuppression, grafts in GKO hosts show less chronic vascular rejection, indicating that IFN-␥ accelerates graft vessel disease (8,35,36). Similarly in the special circumstance of nonvascularized class IIdisparate skin allografts, IFN-␥ is actually essential for graft rejection (7,37). Thus, the net effect of IFN-␥ will depend on the details of the system studied: whether the graft is vascularized, whether there are strong antigenic differences, whether temporary immunosuppression is used, and the time posttransplant.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of IFN-␥ is usually considered to promote tissue injury, which it does effectively in autoimmunity (5) and in some transplant models. For example, IFN-␥ is needed for rejection of established islet transplants by CD8 T cells in a TCR-transgenic model (6), for rejection of class II-disparate skin grafts (7), and aggravates chronic vascular injury in heart transplants (8 -10). Yet despite the association of IFN-␥ with inflammation and MHC regulation, mice with disrupted IFN-␥ genes (GKO mice, BALB/c mice with disrupted IFN-␥ genes) reject transplants briskly (11)(12)(13).…”
mentioning
confidence: 99%